Understanding knowledge construction in a Chinese university EMI classroom: A translanguaging perspective. (June 2023) - Jiang, Anne Li; Zhang, Lawrence Jun
Abstract: Recently interest has been burgeoning in exploring translanguaging as a powerful pedagogical approach to facilitating teaching and learning in various English-medium-instruction (EMI) contexts. However, how knowledge is constructed and communicated through language and other semiotic recourses in mainland Chinese university EMI classrooms has not gained sufficient attention. To enrich and extend research on this topic, this case study examined how translanguaging was enacted and contributed to knowledge construction in a naturally occurring Electronic Business EMI classroom in a mainland Chinese university classroom. Two teachers and their students (N = 36) were involved and data were collected through lesson observations and video-stimulated-recall-interviews. Findings show that teachers' monologic lectures featured four translanguaging practices, namely, cross-language labelling, recapping, code-mixing, and resorting to multimodal resources, whereas in teacher-student interactions, reformulation in English as the L2, code-mixing, and spontaneous use of the L1 were identified. Translanguaging was found to contribute to knowledge construction through operating common as well as distinctive pedagogical, cognitive and social-affective functions in the two discursive activities. The implications for designing and appropriating situated and fine-tuned university EMI translanguaging pedagogy and for EMI teachers' professional development are then discussed. Highlights: Tanslanguaging functions as cognitive scaffolding in monologic lecturing. Translanguaging serves as modelling, engaging, and participating in dialogic interactions. " Trans -" approach to EMI pedagogy should be responsive to specific discursive activities and lesson content.